The mind of St Paul. - Barclay, William, 1907-1978. (New York, Harper, 1958)
A critical study of the letters of Paul, explicating his thought concerning such topics as the Incarnation, the Crucifixion, the Resurrection, faith, grace, and sin.
Keywords: Bible. -- Theology; Paul, -- the Apostle, Saint